Life Cycle Assessment with BIM Towards Sustainable Energy Policy-Making: The Case of Urban Transformation in Istanbul - Yayla, Alperen; Kayakutlu, Gulgun; Kayalica, M. Ozgur (International Journal of Sustainable Construction Engineering and Technology, 2021)
Buildings are responsible for almost forty percent of global energy. Due to their high consumption of energy, buildings are on the front line of sustainability researches. In Turkey, six million out of twenty-two million buildings need to be demolished and rebuilt to meet seismic standards. These buildings are also far below the standards in terms of energy efficiency. Therefore, urban transformation can be thought of as a great opportunity for energy efficiency. This study investigates four things: (i) the energy-efficient urban transformation strategy in GaziosmanpaÅŸa-Istanbul region, which is selected as a case study; (ii) the effect of energy efficiency in this market; (iii) the adequacy of energy standards of Turkey; and (iv) contribution of digitalization in construction to sustainability with Building Information Modelling (BIM) and energy analysis. According to the energy efficiency scenarios, energy analyses were carried out on the BIM model. The most cost-effective strategy was determined with the Life Cycle Cost method. When compared with the current situation, it is possible to save energy up to 227 GWh a year, which is equal to the annual heating energy demand of approximately 30,000 housing, in the case study area with the most efficient scenario to be realized.